Digitalization and Digital Transformation of the Thermal-Power Industry as a Factor of Improving the Thermal Infrastructure Efficiency (a Review) - Golovina, E. Yu; Samarkina, E. V.; Buinov, N. E.; Evloeva, M. V. (Thermal engineering, 2022)
— Innovative development is a key factor for achieving more efficient performance of fuel-and-energy complex (FEC) enterprises, and also more reliable and economically efficient supply of energy to consumers on the basis of state-of-the-art technologies with transforming them into an intelligent core of the thermal-power industry’s technological infrastructure. Information technologies continue to actively penetrate into all key fields of human activity and economy sectors; they are a condition for competitiveness and economic development of the country and for further improvement in people’s quality of life. The current stage of this process has been defined as “digital transformation.” It is characterized by an entirely new feature: digital technologies transfer from the category of auxiliary tools to the category of capital goods. This process also has touched the fuel-and-energy complex. Transition to a digitalized operation mode is a response to external technological challenges and future structural changes in the power system. The article studies the goals pursued by digital transformation of thermal-power industry companies. The influence of the thermal-power industry’s digitalization and digital transformation on energy saving and improvement of energy efficiency and energy infrastructure performance quality is considered. Practical experience of implementing digital technology introduction projects aimed at energy-efficient upgrading of heat-supply systems is presented. Fundamental works of foreign and domestic authors in the field of digital economy are considered. Based on the study results, a refined system of concepts is presented; the authors’ own approach to digital transformation components is proposed, and categories lying at the heart of Industry 4.0 are identified, which include a certain set of digital technologies, including prospective ones, from the viewpoint of applying them in the thermal-power industry.